Intentional social action in virtual communities - Bagozzi, Richard P.; Dholakia, Utpal M. (Journal of interactive marketing, 2002)
There is growing evidence of the increasing participation in, and influence of, virtual communities in digital environments. To help explain this irresistible allure, the individual and social determinants of the member's intentions to participate are investigated. Conceptualizing virtual community participation as intentional social action, we explicate the concept of “we-intentions”, and use the Model of Goal-Directed Behavior to explain members’ we-intentions. Virtual community influences pertaining to compliance, internalization, and social identity are also elaborated on. An empirical study of regular virtual community participants ( N = 157) finds that we-intentions to participate are functions of both individual determinants (positive anticipated emotions and desires), and community influences (social identity). Implications for marketing and future research opportunities are discussed.